The role of persistent primitive reflexes in learning difficulties : an evaluation of a new causal theory of dyslexia - McEvoy, Maria (Trinity College (Dublin, Ireland). School of Psychology, 2003)
In a recent study in Belfast by McPhillips, Hepper and Mulhern (2000) the persistence of an early motor reflex, the asymmetric tonic neck reflex (ATNR) was linked to dyslexia. A 100% prevalence of the ATNR was reported in a sample of children with specific reading difficulties. A movement programme involving repetition of reflex movements was reported to have significantly reduced the persistent primitive reflex. This, in turn, led to an improvement of performance in reading. If the persistent ATNR causes both a maturational lag and is reliably associated with dyslexia, then it may constitute both a neurological cause and indicate a definite treatment. However, the McPhillip’s study did not use a control group who did not have reading difficulties when testing for the prevalence of the ATNR and so it may be that the ATNR is present in most or all of the population and not just a sub-population of dyslexic children as the work of other research has shown (e.g., Parmenter, 1975). This research attempted to assess both the normal and dyslexic population for prevalence of the ATNR. A second aim of the study was to assess the prevalence of one other motor reflex, the tonic labyrinthine reflex (TLR) because of its link in the literature with reading achievement. A third aim of the study was to investigate the finding by Parmenter (1975) that the ATNR manifested more powerfully when the child’s head was turned to the right, in contrast with the left. A fourth aim of the study was to contrast the ATNR measurement method used by McPhillips, the Schilder test, with another method, the Ayres II test, which was used by Parmenter, to determine the reliability of the measurement procedure. Finally, the relationship between the TLR and ATNR was analysed in order to test the theory that the TLR predates the ATNR and must be integrated fully, before the ATNR can be integrated. The Ayres test for the ATNR was the only reflex measure that significantly discriminated between dyslexic and non-dyslexic children. Both of the tests for the ATNR found a difference between sides to which the head was turned but no interaction effect. The Schilder test was found to be a very unreliable measure for measuring the ATNR when compared to the Ayres II test and both measures were found to have a high degree of subjectivity making it difficult to provide conclusive evidence regarding the validity of the hypothesis that persistent reflexes are related to developmental dyslexia. Future research must attempt to standardise reflex measurement methods so that studies can be reliably compared and evaluated. Finally, the ATNR and TLR were not significantly correlated which questions the theory of the evolution of postural reflexes. The theory of persistent reflexes as a causal explanation for dyslexia is not supported by this research. Future research might consider the role of the cerebellum in learning difficulties as this structure has a role in reflex control and tonus and so persistent reflexes may be only a part o f a larger cerebellar system dysfunction rather than the primary cause of dyslexia.
Keywords: Psychology, M.Sc.; M.Sc. Trinity College Dublin